Takayasu disease - Roedenbeck, S. D. (1956)
Takayasu's disease or nonspecific arteritis young woman, was long regarded as a condition typical of the Asian race, a concept that has been distorted by Western publications increasingly frequent. From the clinical point of view is regarded as primarily neurological, cardiovascular and ocular manifestadones those discussed apropos of a personal case: ill 25-year-old with a history of probable tuberculous infection, who has six years a neurological condition characterized by headache paroxysmal, intermittent claudication and visual facio-brachial muscle; then a apoplectic stroke with coma for three days and right hemiparesis discreet; days after a new apoplectic stroke with coma vigil for two and half months, bilateral motor disorders, mixed aphasia a right hemiplegia persisted for seven months and then monopleiía with predominantly distal hypoesthesia brachial until today. The review found no pulse in both upper and left carotid members absent in higher blood pressure and hypertension in the lower extremities. The pathogenesis of vascular disease is briefly discussed, focusing mainly on the importance of aortic arch syndromes in cerebral circulation problems.